Strategi Peningkatan Kinerja SDM di Era New Normal dan Tantangan Work From Home - Wahyudi, Triyono Arief (ABDIMAS Jurnal Pengabdian Kepada Masyarakat, 2021)
The transformation of socio-economic conditions, previously driven by the rapid development of digital technology in the 4.0 era, has become increasingly complex due to the Covid-19 pandemic. Since the first case was announced on March 2, 2020, and declared a national disaster, the pandemic has profoundly changed various aspects of life, including learning methods, worship practices, social interactions, and work patterns. The economic impact has been severe, marked by waves of layoffs, declining public purchasing power, and the closure of numerous businesses. Various industrial sectors have collapsed, distribution chains have been disrupted, and restrictions on imports have been imposed. According to Pakpahan (2020), the most significant implications have occurred in the tourism, trade, investment sectors, and Micro, Small, and Medium Enterprises (MSMEs), which experienced declines in production and trade value. The pandemic has also increased unemployment, posing major challenges to national economic recovery amid global social transformation.